A nomadic subtelomeric disease resistance gene cluster in common bean - David, Perrine; Chen, Nicolas W.G.; Pedrosa Harand, Andrea; Thareau, Vincent; Sévignac, Mireille; Cannon, Steven B.; Debouck, Daniel G.; Langin, Thierry; Geffroy, Valerie (Oxford University Press, 2009)
The B4 resistance (R) gene cluster is one of the largest clusters known in common bean (Phaseolus vulgaris [Pv]). It is located in a peculiar genomic environment in the subtelomeric region of the short arm of chromosome 4, adjacent to two heterochromatic blocks (knobs). We sequenced 650 kb spanning this locus and annotated 97 genes, 26 of which correspond to Coiled-Coil-Nucleotide-Binding-Site-Leucine-Rich-Repeat (CNL). Conserved microsynteny was observed between the Pv B4 locus and corresponding regions of Medicago truncatula and Lotus japonicus in chromosomes Mt6 and Lj2, respectively. The notable exception was the CNL sequences, which were completely absent in these regions. The origin of the Pv B4-CNL sequences was investigated through phylogenetic analysis, which reveals that, in the Pv genome, paralogous CNL genes are shared among nonhomologous chromosomes (4 and 11). Together, our results suggest that Pv B4-CNL was derived from CNL sequences from another cluster, the Co-2 cluster, through an ectopic recombination event. Integration of the soybean (Glycine max) genome data enables us to date more precisely this event and also to infer that a single CNL moved from the Co-2 to the B4 cluster. Moreover, we identified a new 528-bp satellite repeat, referred to as khipu, specific to the Phaseolus genus, present both between B4-CNL sequences and in the two knobs identified at the B4 R gene cluster. The khipu repeat is present on most chromosomal termini, indicating the existence of frequent ectopic recombination events in Pv subtelomeric regions. Our results highlight the importance of ectopic recombination in R gene evolution.